Practical guidance to reduce radiation exposure in electrophysiology applying ultra low-dose protocols: a European Heart Rhythm Association review - Sommer, Philipp; Sciacca, Vanessa; Anselmino, Matteo; Tilz, Roland; Bourier, Felix; Lehrmann, Heiko; Bulava, Alan (Europace, 2023)
Interventional electrophysiology offers a great variety of treatment options to patients suffering from symptomatic cardiac arrhythmia. Catheter ablation of supraventricular and ventricular tachycardia has globally evolved a cornerstone in modern arrhythmia management. Complex interventional electrophysiological procedures engaging multiple ablation tools have been developed over the past decades. Fluoroscopy enabled interventional electrophysiologist throughout the years to gain profound knowledge on intracardiac anatomy and catheter movement inside the cardiac cavities and hence develop specific ablation approaches. However, the application of X-ray technologies imposes serious health risks to patients and operators. To reduce the use of fluoroscopy during interventional electrophysiological procedures to the possibly lowest degree and to establish an optimal protection of patients and operators in cases of fluoroscopy is the main goal of modern radiation management. The present manuscript gives an overview of possible strategies of fluoroscopy reduction and specific radiation protection strategies.
Keywords: Radiation awareness; dávka záření; Radiation protection; Fluoroscopy; Cardiac Electrophysiology; Radiation dosage reduction; Radiation Exposure; srdeční arytmie; radiační expozice; Catheter Ablation; srdeční elektrofyziologie; Arrhythmias, Cardiac; Radiation Dosage; lidé; Humans; Electrophysiologic Techniques, Cardiac; elektrofyziologické techniky kardiologické; Ultra low-dose protocols; katetrizační ablace; fluoroskopie